ORGANIZATIONAL MANAGEMENT TRANSFORMATION IN HEALTHCARE SERVICES: A SYSTEMATIC REVIEW OF DIGITAL INFORMATION SYSTEMS, HUMAN CAPITAL PERFORMANCE, AND PATIENT-CENTERED SERVICE QUALITY - Syaiful Pakaya (CV. Adiba Aisha Amira, 2026)
The increasing complexity of healthcare services in the digital era has intensified the need for organizational management transformation to ensure efficiency, service quality, and patient-centered care. This study aims to systematically review the literature on organizational management transformation in healthcare services, with a particular focus on digital information system integration, human capital performance, and patient-centered service quality. Using a qualitative approach, this study employs a systematic literature review design, analyzing peer-reviewed articles indexed in Scopus. The literature selection adheres to the PRISMA guidelines, and the data are analyzed using thematic analysis to identify dominant patterns and relationships across the studies.The findings reveal that successful organizational transformation in healthcare is driven by the effective integration of digital information systems, supported by competent and adaptive human capital, and aligned with patient-centered service quality objectives. Digital technologies serve as enablers of transformation; however, their impact is highly dependent on an organization's readiness, leadership, and workforce capabilities. Moreover, the review highlights that improvements in service quality and patient experience are more likely to occur when technological adoption is embedded within a holistic organizational transformation strategy rather than implemented as a standalone initiative. This study contributes to the literature by providing an integrative perspective on healthcare organizational management transformation, emphasizing the interdependence between technology, human resources, and patient-oriented service outcomes. Practically, the findings offer valuable insights for healthcare managers and policymakers in designing sustainable transformation strategies that enhance organizational performance and improve patient care quality in the digital age